Performance of the New Version (v2.0) of the GenoType MTBDRsl Test for Detection of Resistance to Second-Line Drugs in Multidrug-Resistant Mycobacterium tuberculosis Complex Strains - Brossier, Florence (J Clin Microbiol, 2016)
Detecting resistance to fluoroquinolones (FQ) and second-line injectable drugs (amikacin [AMK], kanamycin [KAN], and capreomycin [CAP]) is crucial given the worldwide increase in the incidence of extensively drug-resistant tuberculosis (XDR-TB). A new version of the GenoType MTBDRsl test (v2.0) has been developed to improve the detection of resistance to FQ (involving gyrA and gyrB mutations) and to second-line injectable drugs (involving rrs and eis promoter mutations) in Mycobacterium tuberculosis. A collection of 127 multidrug-resistant (MDR) M. tuberculosis complex strains was tested using the first (v1) and second (v2.0) versions of the MTBDRsl test, as well as DNA sequencing. The specificities in resistance detection of v1 and v2.0 were similar throughout, whereas the levels of sensitivity of v2.0 were superior for FQ (94.8% versus 89.6%) and KAN (90.5% versus 59.5%) but similar for AMK (91.3%) and CAP (83.0%). The sensitivity and specificity of v2.0 were superior to those of v1 for the detection of pre-XDR strains (83.3% versus 75.0% and 88.6% versus 67.1%, respectively), whereas the sensitivity of v2.0 was superior to that of v1 only for the detection of XDR strains (83.0% versus 49.1%). In conclusion, MTBDRsl v2.0 is superior to MTBDRsl v1 and efficiently detects the most common mutations involved in resistance to FQ and aminoglycosides/CAP. However, due to mutations not recognized by v2.0 or to the presence of resistance mechanisms not yet characterized (particularly mechanisms related to monoresistance to aminoglycosides or CAP), the results for wild-type strains obtained with MTBDRsl v2.0 should be confirmed by further DNA sequencing and phenotypic drug susceptibility testing.